Muscle Strength and Physical Performance as Predictors of Mortality, Hospitalization, and Disability in the Oldest Old. Issue 6 (6th May 2014) - Legrand, Delphine; Vaes, Bert; Matheï, Catharina; Adriaensen, Wim; Van Pottelbergh, Gijs; Degryse, Jean‐Marie
<x xml:space="preserve">Abstract</x> Objectives To evaluate the predictive value of muscle strength and physical performance in the oldest old for all‐cause mortality; hospitalization; and the onset of disability, defined as a decline in activities of daily living (ADLs), independent of muscle mass, inflammatory markers, and comorbidities. Design A prospective, observational, population‐based follow‐up study. Setting Three well‐circumscribed areas of Belgium. Participants Five hundred sixty participants aged 80 and older were followed for 33.5 months (interquartile range 31.1–35.6 months). Measurements Grip strength, Short Physical Performance Battery (SPPB) score, and muscle mass were measured at baseline; ADLs at baseline and after 20 months; and all‐cause mortality and time to first hospitalization from inclusion onward. Kaplan‐Meier curves and Cox proportional hazards models were calculated for all‐cause mortality and hospitalization. Logistic regression analysis was used to determine predictors of decline in ADLs. Results Kaplan–Meier curves showed significantly higher all‐cause mortality and hospitalization in subjects in the lowest tertile of grip strength and SPPB score. The adjusted Cox proportional hazards model showed that participants with high grip strength or a high SPPB score had a lower risk of mortality and hospitalization, independent of muscle mass, inflammatory markers, and comorbidity. A relationship was found between SPPB score and decline in ADLs, independent of muscle mass, inflammation, and comorbidity. Conclusion In people aged 80 and older, physical performance is a strong predictor of mortality, hospitalization, and disability, and muscle strength is a strong predictor of mortality and hospitalization. All of these relationships were independent of muscle mass, inflammatory markers, and comorbidity.